Analisis Social Media Marketing dalam Membentuk Brand Loyalty Sepatu Lokal di Masa Pandemi Covid-19 - Aqil Aulia Wafda Amin; Inasa Ori Sativa; Oktaviana Purnamasari (UMSU, 2022)
AbstractInternet growth are a thing that human cannot deny. Instead of denying the fact that technology are always growing, human should be find a way to take the benefit from that. Social media marketing is an example of the utilization of internet. Regarding that, Brodo Footwear, a local shoes producer is also doing the social media marketing. This qualitative descriptive research is analyzing how Brodo Footwear use their social media marketing to build their loyal customer network. The fact that Brodo Footwear is doing their marketing on social media and also maximizing the elements to build their loyal costumer network.Keywords: Brodo, Loyal, Social Media, Brand Loyalty